Measuring the Level of Security Awareness of Smartphone Users Among Universitas Malikussaleh Students Using the Fuzzy Analytical Hierarchy Process Method - Andreansyah, Sabda; Ula, Munirul; Afrillia, Yesy (International Journal of Engineering, Science and Information Technology, 2025)
Technology is developing rapidly; its benefits are manifold. The development of technology, especially smartphones, Has become a part of everyday life that cannot be distinguished anymore. The increasing number of smartphone users has also impacted the rising information security and privacy cases caused by a lack of awareness of spam, malware, and phishing. Many users upload personal information such as photos, phone numbers, and addresses without antivirus protection. This study aims to identify security and privacy challenges in smartphone use by measuring problems in the dimensions of attitude (knowledge), knowledge (attitude), and behavior (behavior). There are five focus areas: Backdoor, hardware, and AndroidOS, which is still low compared to applications and permissions. The method used the Analytical Hierarchy Process (AHP) with the Fuzzy concept to measure the level of information security awareness of Malikussaleh University students who use Android phones. The results showed that the overall level of understanding was good (80%). Although the attitude and behavior dimensions showed good awareness, the knowledge dimension was moderate. This may be why information security breaches still often occur among Android phone users. Faculty of Economics, Less Aware: 23 people Unaware: 1 person. Faculty of Social and Political Sciences, Less Aware: 24 people. Faculty of Teacher Training and Education, Less Aware: 21 people. Faculty of Law, Less Aware: 24 people. Faculty of Medicine, Less Aware: 27 people and Aware: 3 people. Faculty of Agriculture, Less Aware: 30 people. Faculty of Informatics Engineering, Less Aware: 70 people and Aware: 5 people. Total Awareness, Less Aware: 199 people, nine people, and Unaware: 1 person.